Obrazy biczowania Chrystusa w wybranych mesjadach pasyjnych z XVII wieku - Drożdżewicz, Monika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
My paper addresses the ways of presenting the Passion of Christ in the 17th century Polish passion messiads. Concentrating on the images of the flagellation of Christ in the narrative poems of Kasper Miaskowski, Abraham Rożniatowski, Wacław Potocki and Wespazjan Kochowski, I analyze the relation of the motifs used by them to the exegetic, the mystic, and the apocryphal traditions. Respectful of their original context, my interpretation of the fragments is supported by a thorough analysis of their structure and use of rhetoric devices. My research allows me to conclude that in order to approach the mysteries of faith, the authors of the messiads used symbolic language as a living faith tradition.
The Images of Christ’s Flagellation in Selected 17th Century Passion Messiads
Keywords: barok; epos polski; literatura pasyjna polska; mesjada; poezja religijna polska; symbolika pasyjna; Baroque; Polish epic poetry; Polish Passion literature; messiad; Polish religious poetry; Passion symbols